2021
DOI: 10.1016/j.ajpc.2021.100201
|View full text |Cite
|
Sign up to set email alerts
|

Association of income and educational attainment in hospitalization events in atrial fibrillation

Abstract: Highlights Investigation of social determinants and atrial fibrillation (AF) is limited. We measured income, education, and hospitalizations in a cohort (n = 339) with AF. Social determinants were related to hospitalization events over median 2.6-years. Addressing social determinants of health may reduce adverse events in AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…34 In addition, our study found higher risk of nonelective hospitalizations for men reliant on a government pension solely (a relatively low level of income), which is in line with a retrospective cohort study among patients 65 years or older in the Netherlands 11 and a study among 339 US adults with a mean age of 72.3 years focusing on any hospitalization. 35 Regarding cause-specific nonelective hospitalization, we found an association between sources of income and nonelective hospitalization due to respiratory conditions, which is in agreement with previous studies on any cause-specific hospitalizations in Europe. 10,36 We also found a tendency toward a higher risk of nonelective hospitalization because of respiratory diseases among those with a low educational level which agrees with results from other studies on any hospitalizations.…”
Section: Current Findings In Context Of Other Evidencesupporting
confidence: 92%
“…34 In addition, our study found higher risk of nonelective hospitalizations for men reliant on a government pension solely (a relatively low level of income), which is in line with a retrospective cohort study among patients 65 years or older in the Netherlands 11 and a study among 339 US adults with a mean age of 72.3 years focusing on any hospitalization. 35 Regarding cause-specific nonelective hospitalization, we found an association between sources of income and nonelective hospitalization due to respiratory conditions, which is in agreement with previous studies on any cause-specific hospitalizations in Europe. 10,36 We also found a tendency toward a higher risk of nonelective hospitalization because of respiratory diseases among those with a low educational level which agrees with results from other studies on any hospitalizations.…”
Section: Current Findings In Context Of Other Evidencesupporting
confidence: 92%
“…Social factors, in particular education and income, influence the incidence, management, and outcomes of cardiovascular diseases, including AF. [15] , [16] , [17] , [18] , [19] Mou et al. have examined the lifetime risk for developing AF according to income and education in the Atherosclerosis Risk in Community (ARIC) study.…”
Section: Introductionmentioning
confidence: 99%
“…Further, social risk factors such as income level and educational attainment may contribute to racial and ethnic disparities in cardiovascular care. 12 , 13 As social risk factors contribute to health outcomes, understanding how they modify procedural use is likewise a priority for developing appropriate strategies to address racial disparities. 14 , 15 , 16 , 17 Social risk factors, such as income, education, and neighborhood socioeconomic status, have been shown to modify racial differences in cardiovascular risk and disease.…”
mentioning
confidence: 99%